About the Sculptor Pedro de Ávila (1678-1755): The Discovery of His Death Certificate and New Works Attributable to Him (BSAA arte, 2020)
The biography of the sculptor Pedro de Ávila (1678-1755) ), the great figure of the Valladolid sculpture of the first third of the 18th centuryt, was incomplete, as the exact date of his death had not been found. In this article, this void will be filled by providing the artist’s death certificate. In addition, a series of new works attributable to him are brought to light, which increases his vast catalogue.
Keywords: Baroque; Baroque sculpture; Valladolid; 18th century; Pedro de Ávila